2021
DOI: 10.21037/apm-20-1607
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia in patients undergoing robot-assisted thoracic surgery: a comparison between thoracic epidural analgesia and intercostal nerve block combined with intravenous patient-controlled analgesia

Abstract: Background: Recently, robot-assisted thoracic surgery (RATS) is increasingly applied to lung or mediastinal tumor surgery. However, appropriate methods of postoperative analgesia for RATS have not been studied.Methods: Patients who underwent RATS at a single university hospital between January, 2017 and March, 2018 were studied retrospectively. Patients were anesthetized with either general anesthesia alone or combined general and thoracic epidural anesthesia. Accordingly, postoperative analgesia was managed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…Regarding thoracotomies in general PVB seemed to be comparable to TEA with no difference in analgesic efficiency or major complications like hematomas but with a lower incidence of hypotension [ 36 ]. In case of robot-assisted thoracic surgery (RATS) there is some data showing lower pain scores and less use of rescue medication using TEA in comparison to PCA combined with intercostal nerve block [ 37 ]. Unknown is the optimal analgesic approach for patients undergoing RAMIE for esophageal cancer so far.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding thoracotomies in general PVB seemed to be comparable to TEA with no difference in analgesic efficiency or major complications like hematomas but with a lower incidence of hypotension [ 36 ]. In case of robot-assisted thoracic surgery (RATS) there is some data showing lower pain scores and less use of rescue medication using TEA in comparison to PCA combined with intercostal nerve block [ 37 ]. Unknown is the optimal analgesic approach for patients undergoing RAMIE for esophageal cancer so far.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, however, nitrous oxide co-used with all three anesthetics might provoke EA even after propofol anesthesia ( 13 ). While EA occurs often after inhalational anesthesia in children ( 2 ), a meta-analysis reported that the conversion from inhalational anesthetics to propofol reduces the incidence of EA in children ( 24 ). Our present results seemed in agreement with such previous data ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In such patients, rapid emergence from anesthesia and adequate postoperative pain control are crucial to achieve early recovery of postoperative respiratory function. To achieve such goals in patients undergoing lung cancer surgery, general anesthesia with desflurane or propofol and remifentanil, combined with thoracic epidural anesthesia, seems a reasonable choice ( 2 ), since desflurane and propofol enable rapid emergence from anesthesia ( 3 - 13 ), adequate intraoperative analgesia provided by remifentanil and/or epidural anesthesia reduces doses of anesthetics required for anesthesia ( 14 , 15 ), ultrashort-acting remifentanil does not cause postoperative respiratory depression ( 16 ), and epidural anesthesia reduces doses of opioids required for intra- and post-operative pain control while providing adequate postoperative analgesia without causing respiratory depression ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In most RATS interventions, multimodal analgesics combined with local anesthesia of the surgical incisions are considered sufficient for pain control [32,22]. Intercostal nerve blockade and submuscular analgesic depositories may be applied additionally [33,34]. Especially patients with an increased surgical likelihood for conversion to thoracotomy should be counselled very differentiated.…”
Section: Preoperative Considerationsmentioning
confidence: 99%